The Implementation of Project-Based Learning Through a Cooperative Approach to Improve Student Activity and Learning Outcomes - Wanda Dea Khairani; Roza Thohiri; Rini Herliani; Silalahi, Sondang Aida; Weny Nurwendari (Equilibrium: Jurnal Pendidikan, 2026)
This study adopted the Project-Based Learning (PjBL) model with a cooperative approach in order to enhance student participation and learning achievement. The research was conducted at SMKN 1 Patumbak, involving all 35 students from class XI AKL 1. The method employed was Classroom Action Research (CAR), which was structured into two cycles, with each cycle consisting of planning, implementation, observation, and reflection phases. Data were collected using student learning activity observation sheets and learning outcome test instruments. The research findings revealed that the application of the cooperative-based PjBL model was able to encourage students to keep progressing over time. This model proved effective, as reflected in the surge of learning activity percentage from 65% in the first cycle to 88% in the second cycle. Student learning outcomes also showed considerable improvement, marked by the pre-test average score of 68.2 which rose to 75.8 in the first cycle, then increased again to 86.7 in the second cycle. Furthermore, classical learning completeness also experienced a jump from 34% to reaching 91%.